Ferritin H-like subunit from Manila clam (Ruditapes philippinarum) : Molecular insights as a potent player in host antibacterial defense - Kim, H.; Elvitigala, D. A. S.; Lee, Y.; Lee, S.; Whang, I.; Lee, J. (Elsevier, 2012)
Ferritins are iron chelating proteins, which involve in iron metabolism and sequestration, contributing to the iron homeostasis in living organisms. In the present study, one ferritin subunit which was identified as H-like subunit was completely characterized in cDNA and protein levels from Manila clam (Ruditapes philippinarum); (RpFeH). The full length cDNA of RpFeH was 776 bp and it consisted of open reading frame of 513 bp, encoding a 171 amino acid peptide with a calculated molecular mass of 19.6 kDa and isoelectric point of 5.23. The amino acid sequence resembled the characteristic features of typical ferritin H subunits, including seven metal ligands in ferroxidase center, two iron binding region signatures and potential bio-mineralization residue (Thy27). Moreover, it was possible to identify an iron response element in 50 untranslated region, showing an agreement with previously reported ferritin H like subunits. The generated 3 dimensional tertiary structure of RpFeH showed a substantial consistency with the human ferritin H subunit, reinforcing its validity. Recombinant RpFeH was overexpressed in Escherichia coli BL21 (DE3) and purified. The recombinant protein showed a detectable iron binding activity according to the results obtained in our iron chelating activity assay. Furthermore it showed a noticeable anti-bacterial activity through suppressing the growth of Vibrio tapetis bacteria. The quantitative real time PCR detected ubiquitous RpFeH expression in tissues examined. However expression was found to be elevated in hemocyte and gill tissues. Transcriptional profile of Manila clam gill tissue, challenged with V. tapetis demonstrated a prolonged significant (P < 0.05) transcriptional upregulations from 12 h post injection to 48 h post injection. Our findings suggest that RpFeH functions as an iron chelating protein subunit in Manila clam while contributing to the innate immune responses against bacterial infections, via its iron withholding function.
Keywords: Ferritin H; Manila clam; Recombinant protein; Iron chelating and antibacterial activity; Transcriptional profiling